2014
DOI: 10.1177/0886260514556108
|View full text |Cite
|
Sign up to set email alerts
|

Factors Mediating the Relationship Between Intimate Partner Violence and Cervical Cancer Among Thai Women

Abstract: Previous research suggests that intimate partner violence (IPV), particularly physical or sexual violence, was associated with cervical cancer. However, there is less work examining the mechanism of the relationship between IPV and cervical cancer. The purpose of this cross-sectional study was to examine psychosocial factors (e.g., stress, social support, self-esteem, and depressive symptoms) as mediators of the relationship between IPV and cervical cancer among 532 Thai women with gynecological problems. Abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 35 publications
0
34
0
1
Order By: Relevance
“…[9] Both IPV and child abuse have been associated with smoking, alcohol abuse and obesity. [6, 12–13] Stress was also found to mediate or explain the observed effect of IPV on cervical neoplasia risk [14]. Thus, stress may directly or indirectly be associated with an increased prevalence of IPV among those with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Both IPV and child abuse have been associated with smoking, alcohol abuse and obesity. [6, 12–13] Stress was also found to mediate or explain the observed effect of IPV on cervical neoplasia risk [14]. Thus, stress may directly or indirectly be associated with an increased prevalence of IPV among those with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…IPV victims, especially the ones of physical and sexual violence, are more likely to have cervical cancer than non-victims. However, the reason for this connection is more psychological than physical [8]. Stress, depressive symptoms, and cervical cancer significantly increase with IPV; while social support and self-esteem largely decrease with IPV.…”
Section: Chinese Women In Americamentioning
confidence: 97%
“…Stress, depressive symptoms, and cervical cancer significantly increase with IPV; while social support and self-esteem largely decrease with IPV. Providing social support and improving selfesteem should be an important aspect in lowering stress and depressive symptoms in cervical cancer treatment [8].…”
Section: Chinese Women In Americamentioning
confidence: 99%
“…Thai researchers have recently observed that partner violence had direct effects on lower social support, increased stress, depressive symptoms and cervical cancer ( p < .01) among 532 women and stress alone mediated the effect of partner violence on cancer. While stress may not cause cancer, stress does influence this disease's process . Partner violence has consistently been associated with increased self‐perceived stress including symptoms of post‐traumatic stress disorder (PTSD) among women with and without cancer .…”
Section: Introductionmentioning
confidence: 99%